2013
DOI: 10.1063/1.4826200
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the conductance of monatomic carbon chain

Abstract: Ab initio calculations show that the conductance of short monatomic carbon chain can be dramatically modified by adhering a single H, N, or O atom to the chain. For example, the conductance of the pristine chain gets about two orders of magnitude smaller if an H atom is adhered to the chain. By a statistical model, the structure of the carbon chain with the single atom adhered is found to be quite stable at room temperature, indicating that the method can be used to tune the conductance of monatomic carbon cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…These NWs show enhanced magnetism, as compared to their bulk (3D) state, and quantized conductance. They are predicted to be technologically useful for spintronics-based devices. , Various studies have been carried out on 1D monatomic chains , including transition elements of 3d series, ,,− 4d series, , 5d series, ,,, and alkali metals. It was found that Pt nanowires exhibit Hund’s rule magnetism, and the magnetic moment increases upon stretching; however, in the bulk state Pt does not show magnetism . Delin et al explored the spin dynamics of atomically thin platinum wires based on first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These NWs show enhanced magnetism, as compared to their bulk (3D) state, and quantized conductance. They are predicted to be technologically useful for spintronics-based devices. , Various studies have been carried out on 1D monatomic chains , including transition elements of 3d series, ,,− 4d series, , 5d series, ,,, and alkali metals. It was found that Pt nanowires exhibit Hund’s rule magnetism, and the magnetic moment increases upon stretching; however, in the bulk state Pt does not show magnetism . Delin et al explored the spin dynamics of atomically thin platinum wires based on first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
“…They are predicted to be technologically useful for spintronics-based devices. 13,40 Various studies have been carried out on 1D monatomic chains 41,42 including transition elements of 3d series, 17,38,43−55 4d series, 17,37 5d series, 17,30,56,57 and alkali metals. 57−59 It was found that Pt nanowires exhibit Hund's rule magnetism, and the magnetic moment increases upon stretching; however, in the bulk state Pt does not show magnetism.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The numerical observations of ILM/DB in two-dimensional carbon materials imply the existence of ILM/DB in the carbon monoatomic chain. The carbon monoatomic chain attracts researcher's attentions because of its characteristics in heat and electric conductance [11,12]. The aim of our research is to investigate whether ILM/DB exists in a carbon monoatomic chain or not and how ILM/DB affects the characteristics of the chain such as heat and electric conductance.…”
Section: Introductionmentioning
confidence: 99%
“…sheet by using a high-energy electron beam has raised some attention [16][17][18][19][20][21][22][23][24][25]. Motivated by the fabrication of stable carbon atomic chains, many theoretical studies were performed on the electronic properties of SCAC nanostructures for their perfect sp2 contact [26][27][28][29]. And their special properties such as spin-split, spin-polarity effect and the remarkable oscillatory conducting behavior, gave rise to numerous studies for designing nanoelectronic devices [30][31][32][33][34][35][36][37][38].…”
mentioning
confidence: 99%